Biological Bases of Immune-Related Adverse Events and Potential Crosslinks With Immunogenic Effects of Radiation - Bardoscia, Lilia; Pasinetti, Nadia; Triggiani, Luca; Cozzi, Salvatore; Sardaro, Angela (Frontiers in Pharmacology, 2021)
Immune checkpoint inhibitors have gained an established role in the treatment of different tumors. Indeed, their use has dramatically changed the landscape of cancer care, especially for tumor types traditionally known to have poor outcomes. However, stimulating anticancer immune responses may also elicit an unusual pattern of immune-related adverse events (irAEs), different from those of conventional chemotherapy, likely due to a self-tolerance impairment featuring the production of autoreactive lymphocytes and autoantibodies, or a non- specific autoinflammatory reaction. Ionizing radiation has proven to promote both positive pro-inflammatory and immunostimolatory activities, and negative anti-inflammatory and immunosuppressive mechanisms, as a result of cross-linked interactions among radiation dose, the tumor microenvironment and the host genetic predisposition. Several publications argue in favor of combining immunotherapy and a broad range of radiation schedules, based on the recent evidence of superior treatment responses and patient survival. The synergistic modulation of the immune response by radiation therapy and immunotherapeutics, particularly those manipulating T-cell activation, may also affect the type and severity of irAEs, suggesting a relationship between the positive antitumor and adverse autoimmune effects of these agents. As yet, information on factors that may help to predict immune toxicity is still lacking. The aim of our work is to provide an overview of the biological mechanisms underlying irAEs and possible crosslinks with radiation-induced anticancer immune responses. We believe such an overview may support the optimization of immunotherapy and radiotherapy as essential components of multimodal anticancer therapeutic approaches. Challenges in translating these to clinical practice are discussed.